Impact of Albedo and Tilt Optimization on the Performance of Bifacial Photovoltaic Panels - Haroun Hanadi; Rahme Pierre; Issa Jimmy S. (E3S Web of Conferences, 2025)
Bifacial solar modules, leveraging solar irradiation on both their front and rear surfaces due to their dual-sided photovoltaic response, have been under investigation since the 1960s and exhibit significant potential over monofacial cells. Their performance is highly influenced by rear side illumination, primarily determined by ground albedo. This study employs the isotropic diffuse model to calculate the total irradiation incident on a bifacial module and examines the impact of varying albedo levels and tilt angles on irradiation. Additionally, the research compares the performance of bifacial panels with monofacial panels under identical conditions. It was found that enhancing ground reflectivity considerably improves bifacial panel performance, with mirrors increasing irradiation by 97%. This demonstrates the substantial effect of albedo on bifacial panels, while monofacial panels remain practically unaffected by variations in ground reflectance.